Screening maize and sorghum for chilling tolerance at seedling stage - Moolakkal Antony, Reshma (Kansas State University, 2018)
Low temperature is one of the most limiting stresses to crops that are adapted to tropical and subtropical regions, such as maize (Zea mays L.) and sorghum [Sorghum bicolor (L.) Moench], when introduced into temperate regions. However, no studies have compared the chilling tolerance of maize and sorghum grown together. Therefore, the objective of this research was to screen maize hybrids and sorghum genotypes for chilling tolerance at the germination and seedling stages. With the hypothesis that grain composition of maize and sorghum could lead to varying chilling tolerance, the seeds were analyzed for concentrations of protein, starch, and amylose. Five commercial hybrids of maize and 18 genotypes of sorghum were maintained in growth chambers for 31 days at two temperatures: a control temperature (25/20 °C, day/night) and at chilling temperatures (11/8 °C for 14 days; 12.5/9.5 °C for 14 days, and 14/11 °C for 3 days). Emergence and seedling height were measured during the experiment. At the end of the experiment, shoot dry weight, root dry weight, and leaf area were determined. Emergence of sorghum under the chilling temperature regime was low (18%). Average height of the emerged sorghum seedlings in the cold temperatures at the end of the experiment was 1.4 cm compared to 55.5 cm in the control treatment. All maize hybrids emerged, but emergence and growth were slowed by the cold temperatures, and average height at the end of the experiment was 4.6 cm compared to 96.1 cm in the control treatment. Shoot dry weight, root dry weight, and leaf area of the sorghum under the chilling temperatures were too small to measure, and, for maize, they were greatly reduced. The results showed that, for sorghum, temperatures should be above 14 °C for emergence, while maize could emerge at lower temperatures. The analyses of the sorghum seeds showed that Redbine 60 and RTx430 had the highest protein concentrations (15.71% and 15.35%, respectively), and Segaolane had the lowest protein concentration (9.83%). Segaolane had the highest starch concentration (72.71%), and RTx430 had the lowest starch concentration (65.31%). There was an inverse relationship between protein and starch concentrations in the sorghum seeds (R2 = 0.69). Amylose concentrations did not vary significantly among the sorghum seeds. The analyses of the maize seeds showed that Dekalb 51-20 and Pioneer 1151 had the highest protein concentrations (10.98% and 10.95%, respectively), and Pioneer 1105 had the lowest protein concentration (9.26%). Starch and amylose concentrations did not vary significantly among the maize seeds.
Keywords: Sorghum; Maize; Chilling tolerance; Seedling stage; Cold tolerance; Grain composition